2012
DOI: 10.4049/jimmunol.1103720
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Generation of Long-lived Human Plasma Cells

Abstract: Plasma cells (PCs), the terminal effectors of humoral immunity, are short-lived unless supported by niche environments in which they may persist for years. No model system has linked B cell activation with niche function to allow the in vitro generation of long-lived PCs. Thus, the full trajectory of B cell terminal differentiation has yet to be investigated in vitro. In this article, we describe a robust model for the generation of polyclonal long-lived human PCs from peripheral blood B cells. After a prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
154
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(166 citation statements)
references
References 69 publications
11
154
1
Order By: Relevance
“…First, we demonstrated upregulated expression of the surface antigen CD138 and increased secretion of IgG by the B cells as differentiation progressed. This is consistent with evidence showing that CD138 expression increases gradually as PCs mature [24,38,39]. Additionally, we observed the effect of APRIL on each differentiation stage of naïve (CD27 À ) B cell in vitro.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…First, we demonstrated upregulated expression of the surface antigen CD138 and increased secretion of IgG by the B cells as differentiation progressed. This is consistent with evidence showing that CD138 expression increases gradually as PCs mature [24,38,39]. Additionally, we observed the effect of APRIL on each differentiation stage of naïve (CD27 À ) B cell in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…Human memory B cells differentiate into long-lived PCs in vitro [24]. In contrast, Huggins et al [23] differentiated human naïve (CD27 À ) B cells into CD138 + PCs but did not show that these cells differentiated into long-lived PCs in vitro.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…3,4 Recently, we and others also demonstrated that IL-6 in combination with APRIL, BAFF, or soluble stromal cell factors supports the generation and survival of long-lived PCs (LLPCs). 5,6 In mammals, oxygen distribution is robustly regulated by the vascular system, which continually distributes oxygensaturated red blood cells throughout the body. Despite the sturdiness of this system, oxygen distribution in the body is not uniform.…”
Section: Introductionmentioning
confidence: 99%